Akuntansi Karbon di Indonesia: Pendorong ESG atau Sekadar Janji Kosong? - Raudhah, Putri Nur; Mukhtaruddin, Mukhtaruddin; Sari, Rela (Jurnal Akuntansi & Keuangan Unja, 2026)
The increasingly urgent issue of climate change has prompted Indonesia to strengthen its commitment to achieving net zero emissions within the next four decades. This commitment is reflected in the adoption of carbon accounting practices linked to environmental, social, and governance (ESG) reporting. This study examines whether carbon accounting in Indonesia serves as an effective driver of ESG reporting or merely represents a symbolic commitment. Using a qualitative approach, this research employs a semi-systematic literature review of 51 articles published between 2021 and 2026, focusing on carbon accounting, emission disclosure, and ESG reporting in Indonesia and emerging markets. The findings indicate that carbon accounting can improve environmental transparency and support both financial and environmental performance, particularly when reinforced by strong corporate governance and regulatory initiatives. However, its implementation remains constrained by the lack of standardized reporting frameworks, voluntary disclosures, limited technical capacity, and ongoing greenwashing practices. The study concludes that the effectiveness of carbon accounting depends on management commitment, regulatory enforcement, and stakeholder oversight.